2016
DOI: 10.1161/circinterventions.115.003479
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-Eluting Stents in Patients With Bare-Metal and Drug-Eluting In-Stent Restenosis

Abstract: S tent implantation constitutes the default strategy during coronary interventions.1,2 Drug-eluting stents (DES) are widely used because of their unique ability to inhibit neointimal proliferation and reduce the restenosis risk.1,2 However, although rare, in-stent restenosis (ISR) still occurs after DES implantation. 3,4 Of concern, several studies have suggested that treatment Background-Treatment of patients with drug-eluting stent (DES) in-stent restenosis (ISR) is more challenging than that of patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 31 publications
1
10
0
Order By: Relevance
“…The mechanism of ISR has not been fully elucidated, the results of study have found that the hypertension, diabetes, number of coronary artery lesions ≥ 2 arteries, LDL-C ≥ 1.9 mmol/L, unstable angina, left anterior descending artery, diameter of stent ≥ 3 mm, the length of stent > 20 mm were independent risk factors for ISR in patients with PCI, targeted preventions should be conducted based on those factors. PCI is currently the main effective treatment option for CHD, especially drug-coated stents have greatly improved the efficacy and prognosis of patients with CHD [10]. Although drugcoated stents can significantly reduce the risk of ISR, the risk of acute heart disease events such as progressive angina or acute myocardial infarction caused by ISR still exists, which seriously affects the outcome after PCI [11].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of ISR has not been fully elucidated, the results of study have found that the hypertension, diabetes, number of coronary artery lesions ≥ 2 arteries, LDL-C ≥ 1.9 mmol/L, unstable angina, left anterior descending artery, diameter of stent ≥ 3 mm, the length of stent > 20 mm were independent risk factors for ISR in patients with PCI, targeted preventions should be conducted based on those factors. PCI is currently the main effective treatment option for CHD, especially drug-coated stents have greatly improved the efficacy and prognosis of patients with CHD [10]. Although drugcoated stents can significantly reduce the risk of ISR, the risk of acute heart disease events such as progressive angina or acute myocardial infarction caused by ISR still exists, which seriously affects the outcome after PCI [11].…”
Section: Discussionmentioning
confidence: 99%
“…Serial coronary angiography was performed at baseline (before and after intervention) and within 36 months’ follow-up. ISR was defined as >50% diameter stenosis at follow-up [ 9 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recently published pooled analysis of the RIBS V and RIBS IV compared the efficacy of EES in patients with BMS-ISR and DES-ISR[ 79 - 82 ]. The study detected clinical and morphological differences of ISR in BMS vs DES, including for the later more focal ISR pattern and delayed onset of presentation.…”
Section: Treatmentmentioning
confidence: 99%